Decentralization and the centre right in the UK and Spain: central power and regional responsibility. Issue 4 (2nd October 2017) - Convery, Alan; Lundberg, Thomas Carl
ABSTRACT: Decentralisation and the centre right in the UK and Spain: central power and regional responsibility. Territory, Politics, Governance . The British Conservative Party and the Spanish Partido Popular (PP) have been hostile, at least at times, to devolving greater power to regions. Although both parties might be expected to support decentralization on economically liberal grounds, in fact both have found it extremely difficult to reconcile their centre-right economic instincts with a deeply ingrained commitment to the integrity of the state. This paper explores the tension in conservative and liberal ideology between supporting sub-state political responsibility through decentralization and supporting strong central government able to take long-term (and potentially unpopular) decisions in times of economic crisis. We examine these two parties in light of Toubeau and Wagner's [2015. Explaining party positions on decentralization. British Journal of Political Science, 45 (1), 97–119] framework, finding that market liberalism can be interpreted differently when it comes to decentralization: both the PP and the Conservative Party have both at different times used economic justifications for a strong central state. The PP continues to hold a conservative view of decentralization and the Conservatives have only recently started to link their market liberalism to a justification for decentralization. Thus, whilst it is possible to construct a liberal economic case for devolving power away from the central state, one does not necessarily follow the other.